Panorama of Present Status of Home Science Subject - L. Vatta, K. Chayal, S. Jindal; S. Bhanwaria (Indian Journal of Extension Education, 2018)
The world is moving at a faster speed with new industrial demands increasing day by day. Therefore, the formal education is attempting to meet the needs of these industry demands by developing skills in students during their study years. Home science as a subject offers various skills to students but the pity is that their skills are not recognized by the industries. So the students are not getting proper jobs in these industries. This is the basic reason behind low enrollment of the students in the subject. Keeping these aspects in mind a research project entitled “Status of Available Training Packages, Development of Entrepreneurial Skills and Identification of Future Needs in Home Science Graduates” was submitted to ICAR, New Delhi. This paper is a part of that study and the objectives of it are to explore present status and general perception about the subject from Home Science teachers and to find out the factors responsible for the less enrollment. An attempt was also made to find out recommendation for future which could help to increase the enrollment. Data was collected through a questionnaire which was mailed to home science teachers during 2017. The results show that rigidity in the mindset of the society regarding the limited scope is the prime cause. Teachers perceive that it is a professional and interesting subject which could be a job provider if we can focus on industry collaboration.